Analysis of The Implementation of Social Forestry Policies in East Kalimantan - Fitriyani Sinaga (Green Publisher Indonesia, 2025)
The factual condition of community dependence on forest resources, especially in the State Forest area, has become one of considerations for theGovernment of President Joko Widodo to the Ministry of Environment issue and Forestry Regulation Permen LHK N0.83 tahun 2016 local communities as the main actors in forest management, covering a total area of 12.7 million hectares which is divided into 5 Social Forestry Schemes. At the same time, currently the forest areas in East Kalimantan, especially Production Forests, have almost been allocated for business permits for the use of timber forest products, either in natural forests (IUPHHK-HA) or plantation forests (IUPHHK-HT) with the totally area already encumbered with these rights 5.619.662 hectares or 44.09% of the total Production Forest. And then remaining area is practically limited, unless it is possible to utilize the Protected Forest and Conservation Forest areas. East Kalimantan in this case plans a PS area of 660 thousand hectares. Referring to the policy, it is necessary to analyze the implementation of the policy using a qualitative analysis method based research on purposive sampling with the unit of analysis being the Central and Regional Governments, Social Forestry Assistance Institutions, academics and social forestry community leaders in East Kalimantan. Research data point are were collected by in-depth interviews as well as secondary data and primary supporting data in the field, namely 2 Hkm schemes and 1 HD. The results showed that the implementation in East Kalimantan are P11.